2020
DOI: 10.1051/0004-6361/201936864
|View full text |Cite
|
Sign up to set email alerts
|

Probing the mid-layer structure of red giants

Abstract: Context. The space-borne missions CoRoT and Kepler have already brought stringent constraints on the internal structure of low-mass evolved stars, a large part of which results from the detection of mixed modes. However, all the potential of these oscillation modes as a diagnosis of the stellar interior has not been fully exploited yet. In particular, the coupling factor or the gravity-offset of mixed modes, q and εg, are expected to provide additional constraints on the mid-layers of red giants, which are loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 58 publications
6
40
0
Order By: Relevance
“…The period spacings from the optimisation are also in agreement with the results of Deheuvels et al (2014). The increase in the coupling factor for subgiant stars is due to a very thin zone where mixed modes are evanescent (Pinçon et al 2020). This is the strong coupling assumption that leads to high transmission between the gravity mode cavity and that of the pressure mode cavity (Takata 2016).…”
Section: Results From Optimisation: Period Spacing and Coupling Factorsupporting
confidence: 79%
“…The period spacings from the optimisation are also in agreement with the results of Deheuvels et al (2014). The increase in the coupling factor for subgiant stars is due to a very thin zone where mixed modes are evanescent (Pinçon et al 2020). This is the strong coupling assumption that leads to high transmission between the gravity mode cavity and that of the pressure mode cavity (Takata 2016).…”
Section: Results From Optimisation: Period Spacing and Coupling Factorsupporting
confidence: 79%
“…Eq. ( 5), we can crudely estimate that ∆π 1 is about inversely proportional to the maximum of the Brunt-Väisälä frequency in the radiative region, which was shown by Pinçon et al (2020) to be approximately proportional to the square root of the helium core density. The evolution of the helium core density as a function of its mass is plotted in Fig.…”
Section: Period Spacing ∆πmentioning
confidence: 89%
“…This matches the observations for the pressure offset, indicating that the pressure offset holds an information about the density contrast and the structure in the evanescent region. Indeed, Pinçon et al (2020) showed that the structure of the intermediate evanescent region behaves as power laws of the radius when the density contrast between the core and the evanescent region is large, independently of the stellar mass. This also goes for the Brunt-Väisälä and Lamb frequencies, In contrast, the structure deviates from such a configuration for lower core-envelope density contrast as observed in subgiant stars (see also discussion in Sect.…”
Section: Pressure Offset Pmentioning
confidence: 99%
See 1 more Smart Citation
“…-The mean core rotational splitting, δν rot,core , is a proxy of the mean core rotation rate and was measured for almost 900 stars on the RGB (Gehan et al 2018) and 200 stars in the red clump (Mosser et al 2012b). -The coupling factor, q, characterises the strength of the coupling in the evanescent region between p and g waves and was measured for about 5000 RGB and red clump stars (Mosser et al 2017a;Pinçon et al 2020). -The gravity offset, ε g , provides information on the stratification occurring in the radiative region and was measured for almost 400 stars both on the RGB and in the red clump (Mosser et al 2018;Pinçon et al 2019).…”
Section: Introductionmentioning
confidence: 99%